Do potential migrants internalize migrant rights in OECD host societies?. (25th October 2020) - Beine, Michel; Machado, Joël; Ruyssen, Ilse
Abstract: This paper analyzes how countries' provision of migrant rights affects potential migrants' destination choice. Combining data on bilateral migration desires from over 140 origin countries and data on migrant rights in 38 mainly OECD destination countries over the period 2007–2014, we find that potential migrants tend to favour destinations that are more open to the inclusion of immigrants into their society. In particular, better access to and conditions on the labour market as well as access to nationality and to permanent residency significantly increase the perceived attractiveness of a destination country. These results are robust across different specifications and hold for subsamples of origin countries as well as of destinations. Moreover, some results vary across types of respondents. Educational opportunities for migrants, for instance, affect the migration desires of individuals aged 15 to 24, but less so of individuals in other age groups. Résumé: Les migrants potentiels internalisent‐ils les droits des migrants en vigueur dans les pays d'accueil de l'OCDE ? Cet article étudie comment la disposition de droits pour les migrants dans les pays affecte le choix de destination formé par les migrants potentiels. En combinant des données sur les intentions de migration bilatérale à partir de 140 pays d'origine avec des données relatives aux droits des migrants dans 38 pays principalement de l'OCDE pour la période 2007‐2014, nous montrons que les migrants potentiels préfèrent des destinations qui sont plus ouvertes à l'intégration des immigrants dans leur société. Plus spécifiquement, un meilleur accès aux conditions du marché du travail ainsi que l'accès à la nationalité et à la résidence permanente augmentent de manière significative l'attractivité perc¸ue d'un pays de destination. Ces résultats sont robustes parmi plusieurs spécifications et sont valables sur des sous‐échantillons de pays d'origine et de destination. En outre, certains résultats varient par type de répondants. Ainsi, les possibilités en matière d'éducation affectent les intentions de migrations des individus âgés entre 15 et 24 ans, mais affectent moins celles des individus des autres groupes d'âge.